PERANCANGAN MEDIA INFORMASI TENTANG PARENTING DALAM PERSPEKTIF AGAMA ISLAM - Zhafir Ar Raihan (VCoDe : Visual Communication Design Journal, 2025)
Parenting is an important foundation in shaping the character and morals of future generations. However, as time goes by, many parents face challenges in implementing Parenting patterns that are in accordance with Islamic teachings. This design focuses on developing information media with a two-dimensional animation concept that is communicative, educational and easily accessible as a solution to increase understanding and Parenting skills based on the Islamic religion. Design methods through observation, questionnaires, interviews and literature study. This media design technique uses 5W+1H analysis. The two-dimensional animation design process goes through several stages, namely brainstorming, sketching, storyline and storyboard, the resulting work design is in the form of a two-dimensional animation entitled Ali Cahaya Keluarga, supporting information design, namely posters, x-banners and merchandise (t-shirts, tote bags, keychains). and stickers).